REKONSTRUKSI PENAFSIRAN TENTANG AYAT–AYAT AURAT PEREMPUAN DI NUSANTARA PERSPEKTIF MUHAMMAD SYAHRUR - Fathony, Alvan; Afif Hamid, Abdur Rahman Nor (JURNAL ISLAM NUSANTARA, 2020)
The problem aurat of woman is becoming a utopian reference for women living in Indonesia, due to the shift in the changing function of clothing from covering the aurat to simply a lifestyle. The result of this is the way women dress, how to make them look attractive wearing them, not how to make them comfortable wearing them. Thus the author brings together the thoughts of Muhammad Syahrur on this phenomenon which for the author is considered a problem in this predominantly Islamic country, namely Indonesia. This study uses a research library research method which is still relevant to the situation of Islamic law across the ages, especially in Indonesia. The aim is to try to reveal the thoughts of Muhammad Syahrur who use the hudud theory in interpreting Quranic verses, especially aurat of women verses which are considered controversial with mufassirs and fuqoha, in this case must be competible with Indonesian culture. The results of the literature review show that in the view of Muhammad Syahrur, the reactualization of the aurat of women text by understanding and studying the Koran is highly dependent on the socio-cultural context. Syahrur tried to apply his understanding of the texts of the Quran in the reality of life. According to him, the provisions of the Quran are elastic in that we can adjust the Quranic text depending on the context and conditions of the times.